Restored kelp facilitates lobster recruitment but not other mid‐trophic macroinvertebrates. Issue 7 (9th May 2022) - Shelamoff, Victor; Layton, Cayne; Tatsumi, Masayuki; Cameron, Matthew J.; Wright, Jeffrey T.; Johnson, Craig R.
Abstract: The patch dynamics of foundation species profoundly affects community assembly and thus has important implications for ecosystem restoration. However, it is unclear how restored kelp patches that vary in size and density will influence the establishment of mid‐trophic level (MTL) macroinvertebrates, a key functional group in coastal ecosystems. Artificial reefs with transplants of the canopy‐forming kelp, Ecklonia radiata, were used to quantify the effect of patch size and kelp density on the densities of MTL macroinvertebrates (primarily decapod crustaceans) and on the recruitment of an ecologically important and commercially valuable lobster species. Densities of MTL macroinvertebrates, which were dominated by hermit crabs, decreased with increasing patch size but responded inconsistently to kelp density. There was, however, an overall positive relationship between MTL macroinvertebrates and the density of small epifaunal grazers (a potential food source), along with a negative association with cover of understorey foliose algae. In contrast, the total abundance and density of lobster recruits was higher on larger reefs, and reefs with kelp had up to double the number of recruits relative to reefs with no kelp. After 12 months, most of the surviving lobster recruits occurred on reefs supporting low and medium densities of kelp. These results show that patchy reef substratum is effective in supporting high densities of some MTL macroinvertebrates, irrespective of kelp presence. Although conversely, larger reefs with restored kelp at natural – or even relatively low – densities appear critical to the recruitment of lobsters, which could motivate and provide positive feedback for kelp restoration projects in some locations. Patch dynamics may be used to support restoration efforts by helping to accelerate the recovery of key species and ecosystem services; however, trade‐offs will exist through different taxa responding to patch characteristics in different ways, some positive and some negative.